Historical records of the Buffs, East Kent Regiment (3rd Foot) - Moody, R. S. H. (Richard Stanley Hawks), 1854-1930; Alexander, Herbert, 1874-1946; Butler, Elizabeth (Elizabeth Southerden Thompson), 1846-1933; Paget, Arthur, 1851-1928 (Salt Lake City, UT : Project Gutenberg, 2024)
"Historical Records of the Buffs, East Kent Regiment (3rd Foot) : Formerly" by Colonel R. S. H. Moody is a historical account written in the early 20th century. This work chronicles the history and experiences of the Buffs regiment during World War I, spanning from 1914 to 1919. The book aims to document the regiment's significant role in various battles and engagements, highlighting the bravery and sacrifices of the soldiers who served. The beginning of the historical records offers a preface that contextualizes the importance of the regiment's history during the pivotal years of World War I while setting the stage for the intricate narratives to follow. It discusses the need for a condensed account of the regiment$1 (Bs activities amid overwhelming odds, the bravery displayed, and the high rates of casualties endured. The opening chapters introduce the onset of the war, moving through events such as the mobilization of troops, initial conflicts, and detailed accounts of specific battles. The narrative emphasizes the valor of the soldiers and the evolving nature of warfare against the backdrop of early 20th-century military strategy. (This is an automatically generated summary.)s
The First Battalion goes to war -- The Second Battalion takes its share -- The preparation and the start of more battalions -- The Western Front: Loos -- The Turkish enemy -- The Somme -- A year at Salonica -- With Maude in Mesopotamia -- Palestine -- The Western Front -- The Queen's Own Rifles of Canada -- The end of the Salonica and Mesopotamia campaigns -- Holding on -- The grand result -- Conclusion.
Release date is 2024-03-13
Brian Coe, Karin Spence and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: World War, 1914-1918 -- Regimental histories -- Great Britain; Great Britain. Army. Regiment of Foot, 3rd (East Kent)